Molecular analyses provide insight into mechanisms underlying sarcopenia and myofibre denervation in old skeletal muscles of mice - Barns, M.; Gondro, C.; Tellam, R.; Crabb, Hannah; Grounds, M.; Shavlakadze, T. (Elsevier, 2014)
Molecular mechanisms that are associated with age-related denervation and loss of skeletal muscle mass and function (sarcopenia) are described for female C57Bl/6J mice aged 3, 15, 24, 27 and 29 months (m). Changes in mRNAs and proteins associated with myofibre denervation and protein metabolism in ageing muscles are reported, across the transition from healthy adult myofibres to sarcopenia that occurs between 15 and 24 m. This onset of sarcopenia at 24 m, corresponded with increased expression of genes associated with neuromuscular junction denervation including Chnrg, Chrnd, Ncam1, Runx1, Gadd45a and Myog. Sarcopenia in quadriceps muscles also coincided with increased protein levels for Igf1 receptor, Akt and ribosomal protein S6 (Rps6) with increased phosphorylation of Rps6 (Ser235/236) and elevated Murf1 mRNA and protein, but not Fbxo32: many of these changes are also linked to denervation. Global transcription profiling via microarray analysis confirmed these functional themes and highlighted additional themes that may be a consequence of pathology associated with sarcopenia, including changes in fatty acid metabolism, extracellular matrix structure and protein catabolism. Ageing was also associated with increased global gene expression variance, consistent with decreased control of gene regulation.